TGF-β/Smad3 Signaling Promotes Renal Fibrosis by Inhibiting miR-29 - Qin, Wei (American Society of Nephrology, 2011)
TGF-β/Smad3 signaling promotes fibrosis, but the development of therapeutic interventions involving this pathway will require the identification and ultimate targeting of downstream fibrosis-specific genes. In this study, using a microRNA microarray and real-time PCR, wild-type mice had reduced expression of miR-29 along with the development of progressive renal fibrosis in obstructive nephropathy. In contrast, Smad3 knockout mice had increased expression of miR-29 along with the absence of renal fibrosis in the same model of obstruction. In cultured fibroblasts and tubular epithelial cells, Smad3 mediated TGF-β(1)-induced downregulation of miR-29 by binding to the promoter of miR-29. Furthermore, miR-29 acted as a downstream inhibitor and therapeutic microRNA for TGF-β/Smad3-mediated fibrosis. In vitro, overexpression of miR-29b inhibited, but knockdown of miR-29 enhanced, TGF-β(1)-induced expression of collagens I and III by renal tubular cells. Ultrasound-mediated gene delivery of miR-29b either before or after established obstructive nephropathy blocked progressive renal fibrosis. In conclusion, miR-29 is a downstream inhibitor of TGF-β/Smad3-mediated fibrosis and may have therapeutic potential for diseases involving fibrosis.